The comparison of reading interests of public and private high school students in Tagaytay City and Silang, Cavite - Paras, Bernice B. (2006)
The study identified, analyzed and compared the reading interests of 541 high school students from four diverse private and public schools in Tagaytay City and Silang, Cavite. Respondents were from Tagaytay City Science National High School and General Vito Belarmino National High School, Kalubkob, Silang, Cavite (public schools) and Adventist University of the Philippines Academy, Puting Kahoy, Silang, Cavite and Cavite Institute, Iba, Silang, Cavite (private schools). Majority of the respondents or 86 percent were aged 13 to 16 years old. Of the 541 who participated, (383 or 71 percent) were female.